The First Ptilodactyla Illiger, 1807 (Coleoptera: Dryopoidea: Ptilodactylidae) Described from Eocene Baltic Amber - Kundrata, Robin; Packova, Gabriela; Kairišs, Kristaps; Bukejs, Andris; Hoffmannova, Johana; Blank, Stephan M (Biology, 2021)
The beetle family Ptilodactylidae contains more than 500 extant species; however, its fossil record is scarce and remains understudied. In this study, we describe a new species of Ptilodactylidae, Ptilodactyla eocenica Kundrata, Bukejs and Blank, sp. nov., based on a relatively well-preserved specimen from Baltic amber. We use X-ray microcomputed tomography to reconstruct its morphology since some of the principal diagnostic characters have been obscured by opaque bubbles. It is the third ptilodactylid species described from Baltic amber, and the first one belonging to the subfamily Ptilodactylinae. Additionally, we summarize the classification, diversity, and distribution of both extinct and extant Ptilodactylidae.
Keywords: Byrrhoidea; fossil; beetles; Ptilodactylinae; X-ray microcomputed tomography; Elateriformia; tertiary; diversity